Simulação numérica da dispersão atmosférica de resíduos gasosos provenientes do aterro comum de Bom Sucesso/PB - Sousa, Erick Ferreira de (Universidade Federal Rural do Semi-Árido, 2018)
The increase in demand for natural resources for energy generation and production of consumer goods leads to a higher generation of solid urban waste by consumers. Inadequate disposal of these wastes results in the production of toxic gases and these together with other pollutants from the burning of waste released into the atmosphere bring harm to human health. In the Bom Sucesso / PB common landfill there is an inadequate disposal of urban solid waste, in addition to the open burning. This burning emits toxic smoke and causes health problems of the population, so it is of fundamental importance to carry out the analysis of the dispersion of the pollutants in this locality, in view of being a pioneering work for the city and region. Thus, it is possible to use computational mathematical simulations using the HYSPLIT model, a hybrid between the Lagrangean and Eulerian approximations. As a general objective of the research, it is proposed to perform numerical simulation of the dispersion of atmospheric pollutants from the Bom Sucesso / PB landfill. The study was carried out in two segments. The field survey was performed by analyzing the gravimetric composition, using the quarrying technique, for the purpose of accounting for the organic fraction, as an estimate of the emission rates of the gases: methane (CH4), sulfuric gas (H2S) and ammonia (NH3). For the purposes of the dispersion evaluation, we used meteorological data obtained from the National Institute of Meteorology (INMET) and, in conjunction with the WRPLOT program, we obtained the wind rose with frequency of direction and velocity, as well as precipitation, temperature , which were of fundamental importance for the classification of atypical days. Finally, before the identification of the atypical days, computational mathematical modeling was carried out using the HYSPLIT model, aiming to estimate the spatialization of pollutant feathers and their concentrations. A higher percentage of plastic was found in municipal solid waste, which is a recyclable material. The common landfill is downstream of the city in the direction of the winds which allows the gases produced not to enter the urban perimeter. The pollutant feathers have higher concentrations in the rainy season, however, the dispersion of the pollutants is higher in the dry period, due to the higher velocities of the winds at that time compared to the rainy season.
Keywords: HYSPLIT; Resíduos sólidos urbanos; Destinação; Gravimetria; Urban solid waste; Destination; Gravimetry; Transport of pollutants; ENGENHARIAS::ENGENHARIA SANITARIA